Spatial and temporal targeting of gene expression in Drosophila by means of a tetracycline-dependent transactivator system. - Bello, B.; Resendez-Perez, D.; Gehring, W.J. (Development, 1998)
In order to evaluate the efficiency of the tetracycline-regulated gene expression system in Drosophila, we have generated transgenic lines expressing a tetracycline-controlled transactivator protein (tTA), with specific expression patterns during embryonic and larval development. These lines were used to direct expression of a tTA-responsive promoter fused to the coding region of either the beta-galactosidase or the homeotic protein Antennapedia (ANTP), under various conditions of tetracycline treatment. We found that expression of beta-galactosidase can be efficiently inhibited in embryos and larvae with tetracycline provided in the food, and that a simple removal of the larvae from tetracycline exposure results in the induction of the enzyme in a time- and concentration-dependent manner. Similar treatments can be used to prevent the lethality associated with the ectopic expression of ANTP in embryos and, subsequently, to control the timing of expression of the homeoprotein ANTP specifically in the antennal imaginal disc. Our results show that the expression of a gene placed under the control of a tetracycline-responsive promoter can be tightly controlled, both spatially by the regulatory sequences driving the expression of tTA and temporally by tetracycline. This provides the basis of a versatile binary system for controlling gene expression in Drosophila, with an additional level of regulation as compared to the general method using the yeast transcription factor GAL4.